BPJS Patients Satisfaction Analysis Towards Service Quality of Public Health Center in Surabaya - Darmawan, Didit; Issalillah, Fayola; Khayru, Rafadi Khan; Herdiyana, Andi Raina Ananda; Putra, Arif Rachman; Mardikaningsih, Rahayu; Sinambela, Ella Anastasya (Media Kesehatan Masyarakat Indonesia, 2022)
Surabaya is a growing city and actively develope basic service innovations through Public Health Center (PHC) such as implementing E-Health services, BPJS p-care, including various quality health services and oriented in increasing patient, family, or public satisfaction in Surabaya. The purpose of the study was to identify the level of satisfaction of Badan Penyelenggara Jaminan Sosial (BPJS) and non-BPJS patients with the quality of health services at Manukan Kulon PHC. This research method was a cross-sectional study. The measuring satisfaction instrument used the patient satisfaction index (Customer Satisfaction Index (CSI)). Meanwhile, the satisfaction dimension used the SERVQUAL Principle by looking at the value of gap between expectation and reality from the aspects of responsiveness, tangibles, assurance, empathy, and reliability. The research sample was determined by simple random sampling and the total samples collected were 110 respondents (67 BPJS patients and 43 non-BPJS patients). The results showed that BPJS patients were more satisfied (CSI 83.9%) than non-BPJS patients (CSI 83.4%). Specifically, BPJS patients’ satisfaction dimension gap related to responsiveness is (0.3), tangibles (-0.3), assurance (0.9), empathy (0.6), and reliability (-1.0.) While non BPJS patients have a satisfaction gap value for responsiveness (- 0.1), tangibles (0.1), assurance (0.1), empathy (0.2), and reliability (0.1). This means that in general, BPJS and Non-BPJS patients are very satisfied with the health services of Manukan Kulon PHC. However, it is necessary to prioritize service improvement on the aspects of responsiveness, tangibles and reliability as expected by patients.